2017
DOI: 10.14814/phy2.13493
|View full text |Cite
|
Sign up to set email alerts
|

MiR‐335 overexpression impairs insulin secretion through defective priming of insulin vesicles

Abstract: MicroRNAs contribute to the maintenance of optimal cellular functions by fine‐tuning protein expression levels. In the pancreatic β‐cells, imbalances in the exocytotic machinery components lead to impaired insulin secretion and type 2 diabetes (T2D). We hypothesize that dysregulated miRNA expression exacerbates β‐cell dysfunction, and have earlier shown that islets from the diabetic GK‐rat model have increased expression of miRNAs, including miR‐335‐5p (miR‐335). Here, we aim to determine the specific role of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
29
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 46 publications
1
29
0
Order By: Relevance
“…In the islets of lean T2D model GK‐rats, we found predominantly upregulated miRNAs whose collective targets are enriched for genes in the insulin exocytotic machinery . Specifically, we validated the direct targeting of Stxbp1 mRNA by miR‐335, and recently shown this miRNA to impair insulin secretion via defective priming of insulin vesicles . We have also found that miR‐130a/b and miR‐152, which are differentially expressed in T2D islets control ATP levels, something that will influence both insulin content and glucose stimulated insulin secretion .…”
Section: The Involvement Of Islet Mirnas In T2dmentioning
confidence: 66%
See 4 more Smart Citations
“…In the islets of lean T2D model GK‐rats, we found predominantly upregulated miRNAs whose collective targets are enriched for genes in the insulin exocytotic machinery . Specifically, we validated the direct targeting of Stxbp1 mRNA by miR‐335, and recently shown this miRNA to impair insulin secretion via defective priming of insulin vesicles . We have also found that miR‐130a/b and miR‐152, which are differentially expressed in T2D islets control ATP levels, something that will influence both insulin content and glucose stimulated insulin secretion .…”
Section: The Involvement Of Islet Mirnas In T2dmentioning
confidence: 66%
“…We have also found that miR‐130a/b and miR‐152, which are differentially expressed in T2D islets control ATP levels, something that will influence both insulin content and glucose stimulated insulin secretion . These miRNAs are not among the most highly expressed miRNAs in islets, and do not have the most evident effect sizes, yet they have important regulatory functions in β‐cell physiology by their regulation of metabolism and/or exocytosis …”
Section: The Involvement Of Islet Mirnas In T2dmentioning
confidence: 86%
See 3 more Smart Citations